Engaging efl students through musical integration: a communicative approach to effective english language teaching - Vega Panata , Mayra Geojana (2025)
This study explores how the integration of musical activities into English teaching can transform the learning experience for EFL students. Aiming to increase interest, motivation, and active participation, the research proposes an enriched communicative approach incorporating musical resources, targeted at sixth-grade students with A1 English level. The mixed methodology combines observations, surveys, and interviews conducted over four weeks, allowing for an evaluation of the real impact of these strategies on classroom performance and interaction. The results indicate that the use of music not only fosters a more dynamic and engaging environment but also improves communicative skills and promotes more meaningful learning. This work reaffirms that, through the creative incorporation of musical resources, teachers can enhance the English teaching-learning process, aligning with contemporary pedagogical principles that prioritize student involvement and interest. The evidence gathered suggests that musical activities are an effective tool to motivate and achieve greater success in language teaching, offering a valuable pedagogical strategy that can be implemented in various educational contexts. Ultimately, this research highlights the importance of innovating language teaching methodologies, promoting practices that make the classroom a more interactive, motivating, and effective space for future teachers and students.